Implementation of Islamic Business Ethics on The Scale of International Trade - Al Naquib, Khaira Nazla; Taufik, Edi Rahmat; Barkah, Barkah; Al Ayubi, Sholahuddin (MUAMALATUNA, 2022)
The inability of a nation to meet all of its demands gave rise to the idea of establishing cooperation between nations, which is one of the causes of international trade. This study aims to ascertain the place of Islamic business ethics and social responsibility in global trade. The role of Islamic business ethics and social responsibility in international business is described and discussed in this study using a qualitative methodology. A literature study was utilized as the data collection method for this study. This method involves gathering information on research from books, scholarly journals, and other pub-appropriate publications used as research sources. The findings of this study suggest that business is seen in Islam as the best route to riches. As a result, all commercial activities must be conducted according to the highest standards of ethics, including refraining from engaging in acts of injustice like usury, fraud, and fraud. It is impossible to overestimate the significance of social responsibility in global business. Because of this, companies need to gain their clients’ trust by facilitating their success and granting them access to their legal rights as consumers.